INOVASI PENGOLAHAN AYAM MENJADI NUGGET AYAM DI KELURAHAN SUSUKAN KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Yunita Khusnul Khotimah (Tahta Media Grup, 2023)
The purpose of this community service activity is to provide an understanding to the community about making chicken nuggets. The target of this community service activity is the PKK group in Susukan Ungaran Timur District, Semarang Regency. Providing an understanding of making nuggets is carried out by organizing a socialization which was previously carried out with a pre-test activity to determine the abilities and knowledge of the participants, delivering materials related to making chicken nuggets, then the next activity is a demonstration and direct practice of making chicken nuggets by the participants, and the last activity is a post-test to evaluate the understanding of the knowledge that has been delivered during the socialization and direct practice. The results of the implementation of community service can be described in the following indicators: 1) Participants can follow the activities from start to finish in a conducive manner. 2) Community Service Participants have an understanding of making chicken nuggets 3) Community Service Participants can practice making chicken nuggets.